Mice with pituitary tumor transforming gene (pttg) knockout demonstrate increased urinary space in renal corpuscles - Varyvoda, O.Yu.; Yashchenko, A.M.; Lutsyk, A.D.; Bilyy, R.O.; Afanasiev, S.V.; Filyak, Ye.Z.; Stoika, R.S. (Вiopolymers and Cell, 2014)
Aim. To investigate the effect of knockout of the pituitary tumor transforming gene (pttg-1) on the morphometric parameters and carbohydrate determinants of the murine renal structures. Methods. Kidneys of the knockout mice in comparison with the wild type mice of BL6/C57 strain of 1 month and 1 year age were subjected to morphometric investigation and lectin histochemistry. Morphometric study was completed using ImagePro Plus and ImageJ software. Glycoconjugates were detected by means of 8 lectins possessing different carbohydrate affinities. Results. Knockout of the pttg-1 gene was accompanied by an increased (approx. 30 %) urinary space within the renal corpuscles, enhanced exposure of the LCA and PNA receptor sites, and reduced binding of the LABA, WGA and SNA lectins. Conclusions. This study suggests the effect of the pttg-1 gene products on processing and exposure of the carbohydrates in renal tissues, apparently affecting ultrafiltration of the primary urine. Мета. Дослідити вплив нокауту гена pttg-1 на морфометричні показники і вуглеводні детермінанти структурних компонентів нирки мишей. Методи. Тест-об’єктом слугували тканини нирки мишей лінії BL6/C57 з нокаутом гена pttg-1 (pttg-КО) і мишей дикого типу (pttg-WT) віком 1 місяць та 1 рік. Морфометричні дослідження проводили за допомогою програмних комплексів аналізу зображень ImagePro Plus та ImageJ. Вуглеводні детермінанти вивчали з використанням набору з восьми лектинів різної вуглеводної специфічності, мічених пероксидазою, з наступною візуалізацією діамінобензидином. Результати. Встановлено, що нокаут гена pttg-1 супроводжується збільшенням сечового простору ниркових тілець у середньому на 30 %, підвищеним експонуванням рецепторів лектинів LCA і PNA, а також редукцією рецепторів LABА, WGA і SNA. Висновки. Отримані результати свідчать про дію продукту гена pttg на процесинг та експонування глікополімерів у структурах нирки, що може впливати на процеси ультрафільтрації первинної сечі. Цель. Исследовать влияние нокаута гена pttg-1 на морфометрические параметры и углеводные детерминанты почки мышей. Методы. В качестве тест-объекта использованы ткани почки мышей линии BL6/C57 с нокаутом гена pttg (pttg-KO) и мышей дикого типа (pttg-WT) в возрасте 1 месяц и 1 год. Морфометрические исследования проводили с помощью программных комплексов анализа изображений ImagePro Plus и ImageJ. Углеводные детерминанты выявляли с использованием набора из восьми лектинов различной углеводной специфичности, меченных пероксидазой, с последующей визуализацией диаминобензидином. Результаты. Нокаут гена pttg-1 сопровождается увеличением мочевого пространства почечных телец в среднем на 30 %, возрастанием экспонирования рецепторов лектинов LCA и PNA, а также редукцией рецепторов LABA, WGA и SNA. Выводы. Полученные результаты свидетельствуют о действии продукта гена pttg-1 на процессинг и экспонирование гликополимеров в структурах почки, что может влиять на процессы ультрафильтрации первичной мочи.